Model Pendidikan Sekolah Informal Berbasis Permainan Edukatif untuk Meningkatkan Kreativitas dan Kepercayaan Diri Anak Usia 6-14 Tahun: Studi Kasus di Sawangan Baru - Nur Aeni Hidayah; Siti Sarah Amelia; Silvia Nida Sandira; Aska Tasya Wildania; Muhamad Shamil Bashayev (LPPI UMN AL WASHLIYAH, 2025)
The 2025 Regular Community Service Program (KKN) of UIN Jakarta in Sawangan Baru developed an informal school model based on educational games designed to enhance the creativity and self-confidence of children aged 6–14 years. This study also examines the extent to which this approach is able to stimulate creativity and build self-confidence in children aged 6–14 years through the interaction between the 4Ps theory of creativity and the concept of self-efficacy. This study used a descriptive qualitative approach. This qualitative approach aims to describe systematically, factually, and accurately the facts and relationships between the phenomena studied. Based on the results of the study, it can be concluded that the informal school based on educational games in Sawangan Baru has succeeded in becoming an alternative learning space that is more participatory, fun, and appropriate to the social conditions of urban communities. This program shows a strong link between creativity and children's self-confidence